Parametric generation and multi-objective optimization of stilted building in Zhuang residence. (February 2019) - Xiong, W; Ye, H L; Jie, W; Li, Q C; Ou, H
Abstract: The construction techniques and construction methods of traditional stilted dwellings are facing the danger of being lost. This paper proposes a parameterization method of stilted dwellings taking the digital construction of stilted dwellings as the starting point to improve the parameterization process of the original stilted dwellings, expanding the construction logic of shape grammar and combining with the multi-objective optimization algorithm. This method takes topography and land range as external constraints, takes economic technical index and total construction cost as optimization objective, also takes building type, floor number and room area ratio as parametric variable. Then using genetic algorithm for multi-objective optimization. Comparing with the original generation method, new method can match a given condition to a suitable form. By changing the original design mode "users demand–design digital model-adjusting size–layout model" to "Input condition– computer generating model – multi objective optimization –layout model and indicator", the design process is systematized and the evaluation system is discussed. It provides a design tool for the architects to intervene in the rural construction and also makes the design of stilted dwellings easier.